A Gα12-specific Binding Domain in AKAP-Lbc and p114RhoGEF. (9th September 2016) - Martin, Joseph W.; Cavagnini, Kyle S.; Brawley, Douglas N.; Berkley, Carrie Y.; Smolski, William C.; Garcia, Ricardo D.; Towne, Autumn L.; Sims, Jonathan R.; Meigs, Thomas E.
AKAP-Lbc is a Rho-activating guanine nucleotide exchange factor (RhoGEF) important in heart development and pro-fibrotic signaling in cardiomyocytes. Heterotrimeric G proteins of the G12/13 subfamily, comprising Gα12 and Gα13, are well characterized as stimulating a specialized group of RhoGEFs through interaction with their RGS-homology (RH) domain. Despite lacking an RH domain, AKAP-Lbc is bound by Gα12 through an unknown mechanism to activate Rho signaling. We identified a Gα12-binding region near the C-terminus of AKAP-Lbc, closely homologous to a region of p114RhoGEF that we also discovered to interact with Gα12. This binding mechanism is distinct from the well-studied interface between RH-RhoGEFs and G12/13 α subunits, as demonstrated by Gα12 mutants selectively impaired in binding either this AKAP-Lbc/p114RhoGEF region or RH-RhoGEFs. AKAP-Lbc and p114RhoGEF showed high specificity for binding Gα12 in comparison to Gα13, and experiments using chimeric G12/13 α subunits mapped determinants of this selectivity to the N-terminal region of Gα12. In cultured cells expressing constitutively GDP-bound Gα12 or Gα13, the Gα12 construct was more potent in exerting a dominant-negative effect on serum-mediated signaling to p114RhoGEF, demonstrating coupling of these signaling proteins in a cellular pathway. In addition, charge-reversal of conserved residues in AKAP-Lbc and p114RhoGEF disrupted Gα12 binding for both proteins, suggesting they harbor a common structural mechanism for interaction with this α subunit. Our results provide the first evidence of p114RhoGEF as a Gα12 signaling effector, and define a novel region conserved between AKAP-Lbc and p114RhoGEF that allows Gα12 signaling input to these non-RH RhoGEFs.